Genetic Diagnosis Using Whole Exome Sequencing in Common Variable Immunodeficiency - Maffucci, Patrick; Filion, Charles A.; Boisson, Bertrand; Itan, Yuval; Shang, Lei; Casanova, Jean-Laurent; Cunningham-Rundles, Charlotte (Frontiers in Immunology, 2016)
Whole exome sequencing (WES) has proven an effective tool for the discovery of genetic defects in patients with primary immunodeficiencies (PIDs). However, success in dissecting the genetic etiology of common variable immunodeficiency (CVID) has been limited. We outline a practical framework for using WES to identify causative genetic defects in these subjects. Whole Exome Sequencing (WES) was performed on 50 subjects diagnosed with CVID who had at least one of the following criteria: early onset, autoimmune/inflammatory manifestations, low B lymphocytes, and/or familial history of hypogammaglobulinemia. Following alignment and variant calling, exomes were screened for mutations in 269 PID-causing genes. Variants were filtered based on the mode of inheritance and reported frequency in the general population. Each variant was assessed by study of familial segregation and computational predictions of deleteriousness. Out of 433 variations in PID-associated genes, we identified 17 probable disease-causing mutations in 15 patients (30%). These variations were rare or private and included mono-allelic mutations in NFKB1, STAT3, CTLA4, PIK3CD, and IKZF1, and bi-allelic mutations in LRBA and STXBP2. Forty-two other damaging variants were found but were not considered likely disease-causing based on mode of inheritance and/or patient phenotype. WES combined with analysis of PID-associated genes is a cost-effective approach to identify disease-causing mutations in CVID patients with severe phenotypes and was successful in 30% of our cohort. As targeted therapeutics are becoming the mainstay of treatment for non-infectious manifestations in CVID, this approach will improve management of patients with more severe phenotypes.